Study of degradation of photovoltaic cells based on A3B5 nanoheterostructures under ionizing radiation - Marina N. Orlova; Sergey Yu. Yurchuk; Sergey I. Didenko; Konstantin I. Tapero (Modern Electronic Materials, 2015)
Solar radiation is a practically inexhaustible and environmentally friendly source of energy. Solar panels are classified as devices very sensitive to radiation. Therefore, the problem of creating radiation-resistant solar panels is quite acute. In operation, solar batteries (SB) are exposed to hard corpuscular radiation (radiation belts, solar and cosmic radiation), resulting in the structure of accumulated violations leading to a gradual deterioration of their electrical characteristics. We have conducted experimental studies of single-degradation characteristics of solar cells (SE) based on GaAs with Ge substrate due to the structural damage produced by irradiation with fast neutrons and electrons and step-by-step irradiation with fast neutrons and electrons at different fluences. Before and after each set of neutron and electron fluence we have measured light current–voltage characteristics (CVC) and photosensitivity spectra of the AOC. We have determined the following parameters from the measured CVC: the fault current, the open circuit voltage, the maximum coefficient of performance (COP) (ratio of maximum power to the product of the flux density of solar energy and the cell area) and the fill factor (the ratio of maximum power to the product of the short-circuit current and voltage idling).